AlGDUM assistance to gum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The International Association for the Development of Natural Gum Plants decided to extend scientific and technical assistance to those countries interested in growing gum plants. The association has selected high-yielding species that will be...